Studies on Anti-Cancer Activity of Lysyl Oxidase from Trichoderma Viride MTCC 167 - Kalra, Shipra; Midha, Kanav; Monika, -; Kaur, Manpreet (International Journal of Applied Sciences and Biotechnology, 2016)
Lysyl oxidase produces H2O2 i.e. ROS by acting on L-Lysyine. In the present study, ROS thus produced has been used by in vitro cytotoxicity assay on ovarian cancer cells thereby achieving 250 percent inhibition. Lysyl oxidase activity was determined spectrophotometrically by Dintrophenylhydrazine (DNPH) reagent. For isolation of lysyl oxidase produced by Trichodermaviride, acetone precipitation and ammonium sulphate precipitation was carried out. The effect of temperature on lysyl oxidase production was determined by incubating the media with 1.5 % inoculum at different temperature ranging from  10 , 20, 30,40,50,60,70 , 80 0C for 72 hr . Anti-tumor properties of Lysyl oxidase was checked using Rhodamine assay and NBT Assay.  Comparative results for Acetone and Ammonium Sulphate precipitation showed that Enzyme activity(U/ml)  of acetone precipitation is 124.6 and 144.3 IU/ml and Protein Content is 1.8 and 2.2 mg/ml with the specific activity 68.4IU/mg and 64.1IU/mg . The optimum enzyme production was found to be at pH 8 and optimum temperature for lysyl oxidase production was 500C with maximum enzyme activity of 0.38 (U/ml). 7th fraction contained highest enzyme activity so the retention time of lysyl oxidase was found to be 7 min. The protein content was also calculated by using Bradford method and it was highest in the 1st fraction and in 6th, 7th and 8th fractions. The specific activity has been improved from 75.1 IU/mg to 86.5 IU/mg. 10 units of lysyl oxidase inhibits 3x104 cells in each well to 82.5% and inhibition achieved at same cell count at 200 units which was 250% as observed with NBT and Rhodamine assay.Int J Appl Sci Biotechnol, Vol 4(1): 57-63